Reproducing of the humidity curve of power transformers oil using adaptive neuro-fuzzy systems - Vasilevskij, V. V.; Poliakov, M. O. (Національний технічний університет "Харківський політехнічний інститут", 2021)
The paper presents a comparative analysis of fuzzy neural networks ofvarious architectures in terms of increasing the accuracy of reproducing the moisture content of transformer oil. For training and testing fuzzy neural networks, the results of continuous monitoring of the temperature of the upper and lower layers of transformer oil during two months of operation used. Considered twenty four variants of the architecture of ANFIS models, which differ in the membership functions, the number of terms of each input quantity, and the number of training cycles. The results of using the constructed fuzzy neural networks for reproducing the dynamics of moisture content of transformer oil during a month of operation of the transformer are presented. The reproducing accuracy was assessed using the root mean square error and the coefficient of determination. The test results indicate the sufficient adequacy of the proposed models. Consequently, the RMSE value for the network constructed using Grid Partition method was 0.49, and for the network built using the Subtractive Clustering method – 0.40509.

Наведено порівняльний аналіз моделей ANFIS різної архітектури з точки зору підвищення точності відтворення кривої вологовмісту трансформаторного масла за результатами контролю температури його верхніх та нижніх шарів. При навчанні та тестуванні моделей ANFIS використовувались результати неперервного контролю трансформаторного масла протягом двох місяців експлуатації. Розглянуто двадцять чотири варіанти архітектури моделей ANFIS, які відрізняються функціями приналежності, кількістю термів кожної вхідної величини та кількістю циклів навчання. Представлені результати використання побудованих моделей ANFIS для відтворення кривої динаміки вологості масла протягом місяця експлуатації трансформатора. Точність відтворення кривої вологості масла оцінювалась шляхом розрахунку кореневої середньоквадратичної помилки та коефіцієнта детермінації. Результати тестувань свідчать про достатню адекватність запропонованих моделей. Значення кореневої середньоквадратичної помилки для моделі, побудованої із використанням методу Grid Partition, становило 0,49, а для моделі, побудованої з використанням методу Subtractive Clustering – 0,40509.
Keywords: cellulose insulation; ANFIS; modeling; целюлозна ізоляція; ANFIS; моделювання